Is the predictive power of previous fractures for new spine and non-spine fractures associated with biochemical evidence of altered bone remodelling? The EPOS study. European Prospective Osteoporosis Study. - Vergnaud, P; Lunt, M; Scheidt-Nave, C; Poor, G; Gennari, C; Hoszowski, K; Vaz, A; Reid, D; Benevolenskaya, L; Grazio, S; Weber, K; Miazgowski, T; et al. (2002)
BACKGROUND: In the European Prospective Osteoporosis Study (EPOS), a past spine fracture increased risk of an incident fracture 3.6 - 12-fold even after adjusting for BMD. We examined the possibility that biochemical marker levels were associated with this unexplained BMD-independent element of fracture risk. METHODS: Each of 182 cases in EPOS of spine or non-spine fracture that occurred in 3.8 years of follow-up was matched by age, sex and study centre with two randomly assigned never-fractured controls and one case of past fracture. Analytes measured blind were: osteocalcin, bone-specific alkaline phosphatase, total alkaline phosphatase, serum creatinine, calcium, phosphate and albumin, together with the collagen cross-links degradation products serum CTS and urine CTX. Most subjects also had bone density measured by DXA. RESULTS: Cases who had recent fractures did not differ in marker levels from cases who had their last fracture more than 3 years previously. No statistically significant effect of recent fracture was found for any marker except osteocalcin, which was 17.6% lower in recent peripheral cases compared to unfractured controls (p<0.05) and this was independent of BMD. CONCLUSION: Past fracture as a risk indicator for future fracture is not strongly mediated through increased bone turnover.